Ten Years of Research on History of Science (Physics): A Bibliometric Analysis - Eva Ayu Yanuarti; Nadi Suprapto (Indonesia Approach Education, 2021)
History of science (HoS), nature of science (NoS), and philosophy of science (PoS) are three fundamental concepts in science and physics education. Specifically, this research explored ten years of research of HoS based on the Scopus database through a bibliometric study. The findings indicated some points: the number of articles in 2011-2020 tended to be stable. Sears dominated research on HoS as the top author. Meanwhile, Isis, Science & Education, and Nature were the top sources of research. The USA was a dominant country in researching HoS, followed by UK and Germany. Paper from Tewksbury et al. in the Journal of Bioscience has gained the most citations. Researchers on the world produced four clusters: historian along centuries, HoS in relating to philosophy and nature of science, HoS in connecting with timeline each country along years, and HoS in relating to university and relevant project. The researchers have also offered an advanced research model related to HoS.